2024
DOI: 10.1161/circresaha.123.323464
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac GR Mediates the Diurnal Rhythm in Ventricular Arrhythmia Susceptibility

Roman Tikhomirov,
Robert H. Oakley,
Cali Anderson
et al.

Abstract: RATIONALE: Ventricular arrhythmias (VAs) demonstrate a prominent day-night rhythm, commonly presenting in the early morning. Transcriptional rhythms in cardiac ion channels accompany this phenomenon, but their role in the morning vulnerability to VAs and the underlying mechanisms are not understood. OBJECTIVE: The objectives are to investigate the recruitment of transcription factors to time-of-day differentially accessible chromatin that underpins day-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 124 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…14 Based on this knowledge, the authors confirmed that GRs can bind and modulate transcriptional targets of I Na and I Kr in a time-of-daydependent chromatin accessibility. 9 Another intriguing finding in this study was that GRs can indirectly regulate the rhythmic transcription of Gja1, a gap junction channel gene responsible for electrical coupling. By using 2 different GR knockout models (GR fl/fl and cardioGRKO), the authors demonstrated that the daily variation of Gja1 was abolished, which was also associated with the loss of increased vulnerability to VA at the active phase, perhaps due to functional loss of the day/night rhythm in electrical coupling.…”
Section: Article See P 1306mentioning
confidence: 74%
See 2 more Smart Citations
“…14 Based on this knowledge, the authors confirmed that GRs can bind and modulate transcriptional targets of I Na and I Kr in a time-of-daydependent chromatin accessibility. 9 Another intriguing finding in this study was that GRs can indirectly regulate the rhythmic transcription of Gja1, a gap junction channel gene responsible for electrical coupling. By using 2 different GR knockout models (GR fl/fl and cardioGRKO), the authors demonstrated that the daily variation of Gja1 was abolished, which was also associated with the loss of increased vulnerability to VA at the active phase, perhaps due to functional loss of the day/night rhythm in electrical coupling.…”
Section: Article See P 1306mentioning
confidence: 74%
“…However, despite these compelling findings, a new study by Tikhomirov et al, published in this issue of Circulation Research, suggests that the simple dimerization model of CLOCK and BMAL1 proteins binding to their cognate ion channel promoters may alone be insufficient to explain circadian-dependent occurrence of VA. In fact, this study points to a new and intriguing concept that suggests that changes in chromatin reorganization may be a critical event underlying the circadian rhythmicity of arrhythmias 9 Next, the authors aimed to identify TFs that may be involved in rhythmic gene expression patterns, which could explain the daily changes in ventricular electrical excitability. GRs (glucocorticoid receptors) were identified as a candidate TF with increased transcription at ZT12.…”
Section: Article See P 1306mentioning
confidence: 99%
See 1 more Smart Citation